Pengaruh Model Pembelajaran Project Based Learning Terhadap Kemampuan Pemahaman Konsep Matematis Pada Materi Sistem Persamaan Linear Dua Variabel - Damayanti, Zahra Septi; Pasaribu, Laili Habibah; Hrp, Nurlina Ariani; Julyanti, Eva (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2024)
Project-Based Learning is a skill that includes the ability to search for information, analyze situations, and identify problems in order to develop alternatives in making decisions. This research aims to determine the effect of the Project Based Learning learning model on the ability to understand mathematical concepts in the material of two-variable linear equation systems. The method used in this research is a type of quantitative research, and the method used is experimental or experimental. This research used a pretest-posttest control group design, the sample was students in class VIII1 and VIII8 of SMP Negeri 2 Rantau Selatan. SMP Negeri 2 Rantau Selatan with a total of 64 students. The results of this research are that there is an influence of using the Project Based Learning learning model on students' ability to understand mathematical concepts.